Increasing the Cruise Range and Reducing the Capital Cost of Electric Vehicles by Integrating Auxiliary Unit with the Traction Drive - Kumar, N. Satheesh (2016)
Poor cruise performance of Electric Vehicles (EVs) continues to be the primary reason that impends their market penetration. Adding more battery to extend the cruise range is not a viable solution as it increases the structural weight and capital cost of the EV. Simulations identified that a vehicle spends on average 15% of its total time in braking, signifying an immense potential of the utilization of regenerative braking mechanism. Based on the analysis, a 3 kW auxiliary electrical unit coupled with the traction drive during braking events increases the recoverable energy by 8.4%. In addition, the simulation revealed that, on average, the energy drawn from the battery is reduced by 3.2% when traction drive is integrated with the air-conditioning compressor (an auxiliary electrical load). A practical design solution of the integrated unit is also included in the paper. Based on the findings, it is evident that the integration of an auxiliary unit with the traction drive results in enhancing the energy capturing capacity of the regenerative braking mechanism and decreases the power consumed from the battery. Further, the integrated unit boosts other advantages such as reduced material cost, improved reliability, and a compact and lightweight design.